Pengaruh Pemanfaatan Teknologi Informasi, Sosialisasi Pajak Dan Penerapan E-Filling Terhadap Kepatuhan Wajib Pajak: Studi Kasus Pada Wajib Pajak Kota Yogyakarta - Djo Kristiana Yolanda Wula Djo (Jurnal Literasi Akuntansi, 2022)
The author conducts reaserch aimed at prove the effect of the use of information technology, tax socialization, application of the e-filling system on taxpayer compliance (a case study of taxpayers in the city of Yogyakarta). The type of research used is quantitative research. The research sample is taxpayers in the city of Yogyakarta. Samples were taken using a non-probability sampling method, namely convenience sampling. The total sample is 120 respondents. Data analysis was carried out with validity and reliability tests, classical assumption tests and multiple linear regression analysis with IBM SPSS 22. The results of this study indicate that information technology has a positive effect on taxpayer compliance, tax socialization has a positive effect on taxpayer compliance, the implementation of e-filling positive effect on taxpayer compliance.